Pengaruh Tingkat Kompetensi, Pengalaman Inseminasi Buatan (IB) Dan Pendidikan Terhadap Peningkatan Angka Kebuntingan Di Kabupaten Tulungagung - Hardika Perkasa, Yuntragus Tri; Mulyaningtyas, Ratna Dewi (Universitas Islam Kadiri, 2025)
This research have purpose to the effect of competency level, insemination experience, and education level on increasing pregnancy rates in cattle in Tulungagung Regency. The background of this study is based on the low pregnancy rate in several areas even though the AI program has been promoted nationally. Tulungagung Regency as one of the areas with the highest cattle population in East Java is a strategic object in this study. The method used is a quantitative approach with data collection techniques through questionnaires, interviews, and observations. The research sample consisted of 40 inseminators selected by purposive sampling. Data analysis was carried out by validity test, reliability test, classical assumption test, and multiple linear regression analysis. The results of the study showed that simultaneously, the level of competency, experience, and education of inseminators had a significant effect on pregnancy rates. Partially, the three variables also had a positive and significant effect. Technical competence and field experience have been shown to increase the success of AI implementation, while education provides a deep understanding of reproductive management. This study recommends increasing training and continuing education for inseminators and strengthening technical support from local governments to optimize the AI program. These findings are expected to be a reference in designing strategies to increase livestock productivity based on improving the quality of human resources.